Expressão heteróloga de uma glicosil hidrolase da Família 18 (cv2736) de Chromobacterium violaceum em Pichia pastoris com potencial antibacteriano - Medeiros, Suelen Carneiro de (2012)
Chitinases are enzymes capable of hydrolyzing chitin, a polysaccharide composed of units of N-acetyl-D- glucosamine, which is abundant in nature. The genome sequence of C. violaceum ATCC 12472 has revealed some genes encoding proteins with potential applications in agriculture and medicine, such as those encoding chitinases. This study aimed to express the protein CV2736 in Pichia pastoris KM71H and to evaluate its antimicrobial potential against microorganism of medical importance. To this purpose, the full ORF (encoding rCV2736 PS+) and a partial sequence of it, encoding a truncated protein without its putative signal peptide (rCV2736PS‒), were cloned into the vector pPICZ α A for expression in P. pastoris. The protein rCV2736 PS+ was detected in the cell-free culture medium of P. pastoris cells harboring the corre sponding expression cassete. The recombinant CV2736PS+ was produced in a heterogeneous manner, and when analyzed by SDS-PAGE, three protein bands with apparent molecular masses of 41. 3, 38.1 and 36. 2 kDa were detected. The protein band with the highest molecular mass (41.3 kDa) was stained with the Periodic acid - Schiff’s reagent, thus showing that this band corresponds to N-glycosylated rCV2736PS+. Furthermore, tryptic peptides identified by mass spectrometry (ESI-MS) confirmed the identity of the expressed protein. The recombinant protein produced without the first 22 amino acids(rCV2736PS‒) showed higher chitinase activity than that found for th e fraction containing rCV2736PS+, despite not being detected by SDS-PAGE. The recombinant protein CV2736PS+, present in the fraction F0/95 from the culture medium of induced cells, was active after heat treatment at 50 °C and its maximum chitinolytic activity was recorded at pH 3.0. This fraction was also able to degrade the synthetic substrates 4-nitrophenyl N,N'-diacetyl -β-D-chitobioside and 4-nitrophenyl N,N',N''-triacet yl chitotrioside, which characterizes an endochitinase activity. Abinitio molecular modeling demonstrated that the polypeptide of CV2736 likely folds as a(β/α)8 barrel (also known as TIM barrel), which is typical of the GH18 family proteins. The fraction F0/95 showed antimicrobial activity against Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus and growth inhibition against Salmonella cholera-suis. The same fraction were evaluated against the yeast Candida albicans, but was not detectable inhibition of this microorganism in the assay. These results suggest that rCV2736 should be further studied as a new anti-bacterial agent.